A class of deterministic external problems equivalent to stochastic external problems in the reliability theory of mechanical systems - Pho, Nguyen Van (Vietnam Journal of Mechanics, 1991)
In this paper, the reliability of the Mechanic Systems is expressed under a new form. Then we propose au iterative method of computing of the Reliability, and apply the obtained results to the some problems of Solid Mechanics.